THE EVALUATION OF THE EFFECTIVENESS OF IMAN AND TAQWA (IMTAQ) PROGRAMS IN THE DISTRICT OF ASAHAN - Salim Salim; Indra Jaya (State Islamic University of North Sumatra Indonesia, 2019)
This study aims to see the extent of the success of the IMTAQ program that has been implemented by the Asahan district government since 2011. A sample of 552 respondents from various elements of society, students, sub-district heads, heads of agencies and institutions in carrying out systematic, comprehensive and integrated religious development activities. The variables studied in this study are input variables which consist of socialization of training, operational funds, media information, implementation instructions and technical instructions, human resources, facilities and infrastructure and implementation organizations. Process variables consist of selection and allocation of funds, evaluation monitoring, executive administration, financial administration and workshops. Output variables consist of appreciation and practice of Imtaq, coaching of the Koran and the preservation of Islamic cultural arts. Analysis used in the form of Structural Equation Modeling (SEM) was developed by Karl Joreskog and Dag Sorbon (1999). The results of this study provide several findings as follows; first, the success of the IMTAQ program in Asahan district is determined by information media, infrastructure and financial administration. Second, the success of the IMTAQ program in Asahan district which has been declared successful in the Coaching factor of the Koran and the factor of the development of Islamic cultural arts. Third, the program increase from the following year to an average of 11%. Research is expected to provide socialization to all program implementers in order to pay more attention to the internal components of the Management Information System which include improvements to; a) human components, b) Hardware Resource, c) Software Resource, d) Resource data. e) Network Resource to be able to carry out management functions related to the implementation of IMTAQ programs such as planning, organizing, controlling and evaluating. Keywords: Evaluation, Iman, Taqwa, Asahan District